Dialogue and Actions in Multicultural Russia - ZANNONI, FEDERICO (2015)
The ALLMEET project promotes actions of intercultural education in Russia through the development of six Intercultural Education Platforms in five different regions. This paper is aimed to disseminate the results gained in the first half (18 months) of the project, focusing on the research findings on the intercultural relationships in five different Russian regions (Krasnoyarsk-Siberia, Moscow, Republic of Tatarstan, Republic of Mari El, Arkhangelsk) and on the theoretical background of the ALLMEET actions, planned through a synthesis of Russian and Western theories on intercultural education.